Design of monopulse antenna loaded with Fabry–Perot cavity. Issue 1 (27th August 2022) - Lu, Kuo; Kou, Na; Yu, Shixing; Ding, Zhao; Zhang, Zhengping
Abstract: A monopulse antenna loaded with Fabry–Perot resonator (FPRC) of X‐band for the application of monopulse radars is designed, fabricated, and measured in this letter. The proposed antenna is composed of an FPRC, a feed source that integrates aperture‐coupled microstrip antennas with a sum–difference comparator. The simulation and measurement have demonstrated that the aperture efficiency of the antenna reaches 46%, and the measured gain of the sum beam is 14.8 dBi which is 4.4 dBi higher than the monopulse antenna without an FPRC. The null depth of the difference beam is under −20 dB. The proposed monopulse antenna is of low‐profile, low cost, and simple structure, which can be applied in radar and wireless communication systems.